Kapabalitas Kelembagaan Pemerintah Daerah Kabupaten Bima Dalam Penanggulangan Bencana - haeril haeril; Nur Anilawati; Suraya Suraya (Pusat Penelitian dan Pengabdian pada Masyarakat Sekolah Tinggi Ilmu Administrasi (STIA) Mataram, 2021)
Institutional capability becomes a measure of understanding and ability of local governments in disaster management efforts. This study aims to analyze and describe the institutional capabilities of the Bima District Government in disaster management. This study used descriptive qualitative method. The results show that Disaster management policies have not become a priority for Regional Government policies, financial resources are still minimal where the budget ceiling in regional disaster management has not met the 1 percent figure, even though according to law it requires at least 1 percent of the APBD, causing integration and coordination ineffective institutions, thus collective efforts to achieve disaster management objectives are also not maximal. In addition, the low disaster resilience index in Kabupaten Bima is still at level 3 based on the Hyogo Frameworks for Actions (HFA) indicator. This explains that the Bima District Government has implemented efforts to reduce disaster risk, but with achievements that are still sporadic in nature due to the absence of institutional commitment and / or systematic policies and weak budgetary support. In addition, data on the level of preparedness and capacity of Kabupaten Bima in the face of various types of disasters is at a low level and is very risky. For this reason, it is very important to involve all SKPDs in mainstreaming Disaster management in every regional policy. Also involving researchers, NGOs, the privat sector, as well as capacity building and community participation as an effort to change the paradigm of disaster management in Bima Regency. In addition, it is necessary to implement a strong disaster management mechanism with a disaster risk reduction perspective.